Heavily Indebted Poor Countries Initiative : Statistical Update. (Policy Papers; Policy Paper ;, 2006)
This document updates the information provided in the September 2005 Heavily Indebted Poor Countries (HIPC) Initiative - Status of Implementation report. It deals exclusively with the enhanced HIPC Initiative, and does not consider the implications of the Multilateral Debt Relief Initiative (MDRI).